General and Simple Method for the Synthesis of 3-nitroformazan Using Arenediazonium Tosylates; Current Organic Synthesis; Vol. 13, iss. 4 - Petunin P. V. Pavel Vasilievich; Valiev R. R. Rashid Rinatovich; Kalinin R. G. Rodion Georgievich; Trusova M. E. Marina Evgenievna; Zhdankin V. V. Viktor Vladimirovich; Postnikov P. S. Pavel Sergeevich (2016, 2016)
Title screen